Pemanfaatan Serat Ampas Tebu Sebagai Bahan Tambah Dalam Campuran Beton - Nuari, Rosa Awalia; Hermansyah, Hermansyah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Concrete is a construction material that is often used in building construction. Concrete is a mixture consisting of coarse aggregate and fine aggregate mixed with water and cement as a binder and filler, and additives are often added. Bagasse fiber has the criteria needed to be used as an added material for strengthening concrete. The variations of bagasse fiber used were 0%, 2.5%, 5%, 7.5% and 10%. The results showed a decrease in the slump value, this was due to the higher variation of bagasse substituted for the weight of cement with the same FAS value, which would reduce the workability of the concrete. The compressive strength of concrete with variations of sugarcane fiber decreased. The highest compressive strength value is found at 0% variation, namely 20.93 MPa, this is due to the greater percentage of bagasse fiber mixture, the concrete that should be filled with aggregate is filled with sugarcane fiber, causing the compressive strength of the concrete to decrease.